Labor market trends and tendencies in hungarian public sector in light of an empirical research - Tóth, Katalin; Juhász, Tímea; Zsigri, Ferenc; Hazafi, Zoltán; Szakács, Gábor; Kovács, Ádám; Poór, József (Studia Mundi – Economica, 2019)
Employee turnover is a current challenge of human resource management in organizations. Staff turnover is regarded as a key performance indicator for Human Resources departments, and a serious rise in its level points to events, issues or problems which may severely hamper the successful and efficient operation of any organization. Hence, in such cases immediate measures should be taken to curtail turnover. The paper reviews briefly current trends of labor market and specific HRM challenges of public services. In this study an empirical research is also introduced. Employees with adequate professional experience represent outstanding value for operational efficiency, a turnover index compiled by on a sectoral basis, highlights the fact that turnover is highest among blue collar workers in the private sector. Surprisingly, within the same group in the public sector turnover is typically low. At the same time, however, our 2017 results show that astonishingly high levels of turnover (even 40%) may also occur in public sector organizations. Public sector in Hungary has provided life long employment but the new labor regulation and labor shortages have drastic changed the particular traits.